2022
DOI: 10.1186/s40798-022-00524-w
|View full text |Cite
|
Sign up to set email alerts
|

Soft Tissue Vibrations in Running: A Narrative Review

Abstract: During running, the human body is subjected to impacts generating repetitive soft tissue vibrations (STV). They have been frequently discussed to be harmful for the musculoskeletal system and may alter running gait. The aims of this narrative review were to: (1) provide a comprehensive overview of the literature on STV during running, especially why and how STV occurs; (2) present the various approaches and output parameters used for quantifying STV with their strengths and limitations; (3) summarise the facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The comparison of both methods revealed that they both methods agree strongly, suggesting that they do reflect the primary contributors to movement. By comparing one versus the other, we can estimate the deviation from rigid-body segments, occurring mainly following an impact/collision with the ground [ 24 , 45 ], and that has been related to the estimated soft tissues deformation [ 14 , 23 ]. Soft tissue motion occurs during movement, and the estimation of soft tissue energy dissipation used here does not fully capture the complexity of soft tissue behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of both methods revealed that they both methods agree strongly, suggesting that they do reflect the primary contributors to movement. By comparing one versus the other, we can estimate the deviation from rigid-body segments, occurring mainly following an impact/collision with the ground [ 24 , 45 ], and that has been related to the estimated soft tissues deformation [ 14 , 23 ]. Soft tissue motion occurs during movement, and the estimation of soft tissue energy dissipation used here does not fully capture the complexity of soft tissue behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been emphasized that runners demonstrated subject-specific responses to footwear interventions [4,9,10,28]. STV were mainly reduced with soft and medium midsole whereas MAX shoe distribution was quite equal among the three midsoles (Appendix S2).…”
Section: Stv Responsesmentioning
confidence: 99%
“…Soft tissues (including muscles, tendons, adipose tissue, ligaments, and skin) exhibit a composite structural organization, resulting in a viscoelastic behavior oscillating in all directions when exposed to a shock [3]. Soft‐tissue vibrations (STV) are oscillatory signals described by their frequency, amplitude, and damping [4]. In endurance running, frequencies of the input signal (GRF) are between 10 and 20 Hz [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the pressure from CGs can enhance athletic performance. Several possible mechanisms have been suggested, such as reducing soft tissue vibration and muscle activation for joint stability ( Valle et al, 2013 ; Play et al, 2022 ), altering proprioceptive feedback and neuromuscular control ( Perlau et al, 1995 ; Bernhardt and Anderson, 2005 ) and coordination ( Birmingham et al, 1998 ), and facilitating blood and lymph circulation and metabolite clearance ( O’Riordan et al, 2023) ; Ibegbuna et al, 2003 ). These mechanisms can be interrelated and hence require further investigation.…”
Section: Introductionmentioning
confidence: 99%